Delays in Diagnosis of Pulmonary Lymphangitic Carcinomatosis due to Benign Presentation - Swati Pandey; Shishir Ojha (Case Reports in Oncological Medicine)
The diagnosis of lymphangitic carcinomatosis is challenging due to the manifestation of nonspecific symptoms and radiographic abnormalities that bear similarity to those of interstitial lung disease. Herein, we report the case of a 53-year-old woman diagnosed with lymphangitic carcinomatosis from metastatic gastric adenocarcinoma, 3 months after her initial presentation.